Tracheobronchial Foreign Body Aspiration Diagnosed with Electrical Impedance Tomography - Robert D. Guglielmo; Robinder G. Khemani (Case Reports in Pediatrics)
Background. Foreign body aspiration (FBA) in children has a high morbidity, and early diagnosis is the key for preventing acute and chronic respiratory complications. To diagnose FBA, commonly used imaging modalities have limited negative predictive value, and rigid bronchoscopy remains as the gold standard. We present a case where the diagnosis of FBA was made in a novel way with electrical impedance tomography (EIT). Case Presentation. A 19-month-old previously healthy boy was admitted with a clinical diagnosis of respiratory failure secondary to bronchiolitis. Chest X-ray showed bilateral lung hyperinflation. He enrolled in a research study which used EIT to measure the effects of high flow nasal cannula (HFNC) on minute ventilation in children with bronchiolitis. On initiation, the patient had near-normal right lung ventilation (98%) and near-absent left lung ventilation (2%). We discontinued the study and alerted the medical team that we suspected FBA. Further imaging (lateral decubitus films and lung ultrasounds) was also obtained, but was not diagnostic. Rigid bronchoscopy was performed and showed a peanut occluding the left mainstem bronchus (LMB). The peanut was removed followed by complete resolution of the patient’s symptoms. Conclusions. We believe this is the first reported case of FBA diagnosed via EIT. EIT has been shown to be a useful but underutilized technology for diagnosing respiratory disease. While FBA remains a relatively common cause of morbidity and mortality in children less than age four, early diagnosis remains difficult and requires vigilance. This case illustrates the challenges of relying on chest films and ultrasound to assist with diagnosis and suggests that EIT in combination with a thorough history and physical exam can be used to confirm the presence of FBA.